If f(x)= 6x+7, determine the value of f(-3)
To evaluate a function at a specific x value simply means to substitute that particular value in place of every occurrence of the variable x.
So, starting from [tex] f(x) = 6x+7 [/tex], we have
[tex] f(-3) = 6\cdot(-3)+7 = -18+7 = -11 [/tex]
Use the rules of exponents to evaluate or simplify. Write without negative exponents 5 • 7^0 =
5 • 7^0 = 35^0
You would ignore the 0. And Just multiply the 7 and 5 to get 35.
If the power of any number is zero then the a⁰ is equal to 1. Then the expression 5 × 7⁰ is equivalent to 5.
What is an equivalent expression?The equivalent is the expressions that are in different forms but are equal to the same value.
The expression is given below.
→ 5 × 7⁰
We know that if the power of any number is zero then the a⁰ is equal to 1.
⇒ 5 × 7⁰
⇒ 5 × 1
⇒ 5
More about the equivalent expression link is given below.
https://brainly.com/question/889935
#SPJ2
Solve for r.
35r−21<−35r+19
70 r − 21 < 19
70r<40
r=4/7
Answer:
r< 4/7
Step-by-step explanation:
Find a unit rate A 13 ounce package of pistachios cost 5.99
take 5.99 divide by 13 and the unit rate is 0.46
Please help :)..............
The 2 points closest to the line is (4,12) and (20, 36)
The slope is the change in Y over the change in x:
Slope = (36-12) / (20-4)
Slope = 24 / 16
Slope = 1.5
So now you have y = 1.5x
To find the equation use the formula (y-y1) = m*(x-x1)
y-12 = 1.5(x-4)
Simplify the right side:
y-12 = 1.5x - 6
Add 12 to each side:
y = 1.5x +6
The answer is the 2nd one.
Nancy biked 2.65 miles in the morning and 3.19 miles in the afternoon. What total distance did she bike?
The answer is 5.84
2.65
3.19
+------
5.84
Step by Step:
2.65 + 3.19 = Answer
Anwer:
A = 5.84 Miles
Comments:
N/A
What is 4/9 - (-2/9)
Hello!
[tex]\frac{4}{9}-\frac{2}{9}[/tex]
First you had to used apply rule -(-b)=b
[tex]\frac{4}{9}+\frac{2}{9}[/tex]
Since the denominators are equal to it should be combine by the fractions.
[tex]\frac{4+2}{9}[/tex]
Then add 4+2=6
[tex]\frac{6}{9}[/tex]
[tex]\frac{4}{9}-\frac{-2}{9}[/tex]
Finally you had to cancel by the common factor of 3.
[tex]=Answer--->\frac{2}{3}[/tex]
Hope this helps! And thank you for posting at here on Brainly. And have a great day! -Charlie :)
Could someone explain this to me????
Answer:
Your answer would be 265
Step-by-step explanation:
Your answer would be 265 because knowing that the lowest temp is a negative number, and you're trying to find the difference between a positive number from a negative number, you would have to add a number to -129 to cancel it out and make it 0. The only number that would do so would be 129. Then by using 129, add 136 to it and you will get your answer, I hope this helps :)
NEED A CORRECT ANSWER NOW!!WILL MARK BRAINLIEST!!
Which sentence contains a misplaced modifier?
A. The teacher shared the poems that her students wrote.
B. My brother ate the candy that i had hidden in my dresser.
C. The children are in the art class that is held at the recreation center.
D. The dogs know several commands that take the obedience class.
Answer:
fvbdsnbgb
Step-by-step explanation:
Solve the Following Equation
2.8=2y
1.y=1.4
2.y=1/2
3y=2.8
4.y=0.6
Solve the following Equation
-3=x/5
1.x=-9/4
2.x=-15
3.x=-3/5
4.x=15
Answer:
2.8 = 2y
1. y= 1.4
Answer:
-3 = x/5
x= -15
Explanation:
To find the variable use the opposite function so if its multiplication find x by dividing and vice versa for division
-12=-2v
whats the value of v
6 because -12/-2 would be positive 2
V=6
divide both sides by -2 to get variable v on one side
-12/-2=6
Natalie and her friends decided to rent 4 lanes at regular cost for a party. Ten people need to rent shoes, and 4 people are members. What is the total cost for the party?
I’ve had this question back when i was in school.
You have to calculate at regular price.
4 x 9.75 = 39
Subtraction time. 10 people are renting, 4 are members
10 - 4 = 6
6 that are nonmembers. 4 members
6 x 3.95 = 23.70
4 x 2.95 = 11.80
Add all those up.
39 + 11.80 + 23.70 = 50.80 + 23.70 = 74.50
Answer: $74.50 :)
find the x and y intercept of the graph of 2(y+0.5)=3.5x+2y
Final answer:
The x-intercept of the graph 2(y+0.5) = 3.5x + 2y is 2/7, and the y-intercept is 0.5.
Explanation:
To find the x and y intercepts of the graph of the equation 2(y+0.5) = 3.5x + 2y, we first simplify the equation. Start by distributing the 2 on the left side:
2y + 1 = 3.5x + 2y. Next, subtract 2y from both sides to get:
1 = 3.5x. Now, to find the x-intercept, set y to zero and solve for x:
x-intercept: y = 0
1 = 3.5x
x = 1 / 3.5
x = 2/7
To find the y-intercept, set x to zero and solve for y:
y-intercept: x = 0
1 = 2y
y = 1 / 2
y = 0.5
The x-intercept is 2/7, and the y-intercept is 0.5.
Tom weighs 168.5 pounds. his 2 year old son, nickolhas, weighs 33.7 pounds. How many times as much as nickolhas does Tom weigh?
He weighs 5 times more
Identify any zeros of y=x^2+4x+5.
A. There are no zeros.
B. (5,0),(4,0)
C. (-1,0),(-3,0)
D. (0,0)
The given quadratic equation y=x^2+4x+5 has no real solutions because the discriminant is negative. Therefore, there are no zeros for this equation, making option A (There are no zeros) the correct choice.
Explanation:The question asks to identify any zeros of the quadratic equation [tex]y=x^2+4x+5.[/tex]To find the zeros, we need to set the equation equal to zero and solve for x. This is typically done using the quadratic formula, which is √x=(-b±√(b^2-4ac))/(2a), where a=1, b=4, and c=5 in our equation.
Substituting these values into the quadratic formula gives: x=(-4±√((4)^2-4*1*5))/(2*1) = (-4±√(16-20))/2 = (-4±√(-4))/2. Since the value under the square root sign (the discriminant) is negative, this equation has no real solutions. Thus, there are no zeros for the given quadratic equation, making option A the correct choice.
Mr. Sloan said that his car was worth $30,000 when he first purchased it however over the last three years it has decreased in value $5400 what integer represents the average decrease in value per year?
Answer:
Average decrease in car's value per year = 1800$
Explanation:
The worth of car bought by Mr. Solan = 30000$
Reduction of car's price = 5400$
Number of years considered for measuring reduction of car's price = 3 years.
Average of values = Total of the values/ Number of values.
Average reduction per year = Total reduction/ Number of years.
= 5400/3 = 1800$
So average decrease in car's value per year = 1800$
Write the word sentence as an equation. Then solve. The product of 15 and a number x is −75.
15x = -75 Divide both sides by 15.
Final answer: -5
hope that helps
Solving the product of 15 and a number x is −75 equals to: -5.
Let the number be x.To write the word sentence as an algebraic equation:
In this exercise, we are required to translate the word sentence into a mathematical (algebraic) expression and solve for the unknown variable (number):
The product of 15 and a number x:
[tex]15(x)[/tex]
Equating the above expression to -75, we have:
[tex]15x = -75[/tex]
Simplifying further, we have:
[tex]15x = -75\\\\x = \frac{-75}{15}[/tex]
x = -5
Therefore, the unknown number is -5.
Read more: https://brainly.com/question/22970937
If a car averages 23.2 miles per gallon of gasoline, how far can it go on 15.25 gallons?
The car goes 23.2 miles every gallon, so with 15 gallons (15 * 23.2 = 348) it can go 348 miles. With the extra .25 that the car has, it can go 0.25 * 23.2 = 5.8 miles. 348 miles plus the 5.8 miles gets you 353.8 miles on 15.25 gallons.
A car that averages 23.2 miles per gallon can travel approximately 353.8 miles using 15.25 gallons of gasoline.
If a car averages 23.2 miles per gallon of gasoline, we can calculate the distance it can travel on 15.25 gallons by multiplying the car's fuel efficiency by the amount of gasoline.
To find the distance:
Multiply the car's average miles per gallon (MPG) by the number of gallons of gasoline.
Distance = 23.2 MPG * 15.25 gallons
Distance = 353.8 miles
Therefore car that averages 23.2 miles per gallon can go approximately 353.8 miles on 15.25 gallons of gasoline.
How do I suppose to solve this question?
omar runs 12 miles in 104 minutes. how many miles does he run per minute?
Omar runs about 0.12 miles per minute.
To find this answer, you simply divide both 104 and 12, by 104. In doing so, you'll get 0.115... miles per 1 minute. Rounding up, you'll get 0.12 miles per minute.
I hope this helps!
(1/x-4)(1/x-4)(1/x-4)
can you show me the work please. I looked up the answer online the answer is 1/(x-4)^3 but why is it that? like idk the steps for it
you are multiplying 3 algebraic fractions together
[tex]\frac{1}{x-4}[/tex] × [tex]\frac{1}{x-4}[/tex] x [tex]\frac{1}{x-4}[/tex]
multiply the numerators together, that is 1 × 1 × 1 = 1
multiply the denominators together, that is
(x - 4 ) × (x - 4 ) × (x - 4 ) = (x - 4)³
thus the product of the multiplication is
[tex]\frac{1}{(x-4)^{3} }[/tex]
6 + 2(x-4) = 12 what is X
How to get answer: [tex]1. \mathrm{Subtract\:}6\mathrm{\:from\:both\:sides}\\1.5. 6+2\left(x-4\right)-6=12-6\\2. Simplify\\2.5. 2\left(x-4\right)=6\\3. \mathrm{Divide\:both\:sides\:by\:}2\\3.5. \frac{2\left(x-4\right)}{2}=\frac{6}{2}\\\\4.Simplify\\4.5.x-4=3\\5.\mathrm{Add\:}4\mathrm{\:to\:both\:sides}\\5.5. x-4+4=3+4\\6. Simplify\\6.6. x=7[/tex]
First distribute the 2 to the values inside the parentheses.
[tex]6+2(x-4)=12[/tex]
[tex]6+2x-8=12[/tex]
Combine like terms. (6+-8)
[tex]6+-8=-2[/tex]
[tex]-2+2x=12[/tex]
Add 2 on both sides of the equation.
[tex]2+-2+2x=12+2[/tex][tex]2x=14[/tex]
Divide both sides by 2.
[tex]\frac{2x}{2}[/tex]=[tex]\frac{14}{2}[/tex]
[tex]x=7[/tex]
The value of x is equal to 7.
Martin is $300 in debt he needs to get the depth down to no more than $100 within the next 8 months if he pays the same amount each month what is the minimum he must pay off each month to manage this
M has to pay at least $200 against his debt over the 8 months. If he is to pay every month the same amount, he must pay (at least) 200/8 = $25 per month to meet his goal
If Ruben has 6 new books for his collection. This increases his collection by 12%. How many books does he have now?
He has 56 books now
If we make a proportion where 6/x=12/100, we can solve for x which will be the 100% or all of the books Ruben has
But now, there are 6 new books making the total 56
helpppp :( 3(x-1) = 2x+9
x equals 12 because
3x-3= 2x+9
x=12
3(x-1) = 2x+9 Remove the Brackets on the left
3x - 3 = 2x + 9 Add 3 to both sides
3x = 2x + 9 + 3 Collect like terms
3x = 2x + 12 Subtract 2x from both sides.
3x - 2x = 2x-2x + 12
x = 12
What is the least common multiple of 7 and 4?
7 x 4 = 28
The least common multiple of 7 and 4 = 28
The answer is 28. I have to type this because it wont let me simply answer your question.
I need help with a review test. Could someone help out with a few answers? I'm struggling to wrap my head around this, and I have a test tomorrow
I can help with a couple of them. You are allowed a maximum of 3 questions per request. You will get more responses if you split the 4-page worksheet into several requests. There are 15 questions so split them into 5 requests.
***********************************************************************************************************
1) Rewrite the equations in y = mx + b format (m = slope, b = y-intercept)
Independent: one solution ⇒ different slopes
Dependent: infinite solutions (same line) ⇒ same slope and y-intercept
Inconsistent: no solutions (parallel lines) ⇒ same slope but different y-intercepts
-21x - 3y = -24 → -3y = 21x - 24 → y = -7x + 8 ⇒ m = -7, b = 8
y = -7x + 7 ⇒ m = -7, b = 7
same slope but different y-intercepts = parallel lines = no solution
Answer: Inconsistent
12) Eliminate a variable for equations 1 and 2, then eliminate the same variable for equations 2 and 3. You will end up with two new equations and two variables. Solve that system by eliminating one of the variables (using any method) and solving for the remaining variable. Then plug that answer into one of the new equations. Then plug in both those answers into one of the original equations.
EQ1: x + 3y + 2z = 8 → 1(x + 3y + 2z = 8) → x + 3y + 2z = 8
EQ2: 3x + y + 3z = -10 → -3(3x + y + 3z = -10) → -9x - 3y - 9z = 30
NEW EQ 1,2: -8x -7z = 38
EQ2: 3x + y + 3z = -10 → 2(3x + y + 3z = -10) → 6x + 2y + 6z = -20
EQ3: -2x - 2y - z = 10 → 1(-2x - 2y - z = 10) → -2x - 2y - z = 10
NEW EQ 2,3: 4x +5z = -10
NEW EQ 1,2: -8x - 7z = 38 → 1(-8x - 7z = 38) → -8x - 7z = 38
NEW EQ 2,3: 4x + 5z = -10 → 2(4x + 5z = -10) → 8x + 10z = -20
3z = 18
z = 6
NEW EQ 2,3: 4x + 5z = -10 ⇒ 4x + 5(6) = -10 ⇒ 4x + 30 = -10 ⇒ 4x = -40 ⇒ x = -10
EQ1: x + 3y + 2z = 8 ⇒ (-10) + 3y + 2(6) = 8 ⇒ 3y + 2 = 8 ⇒ 3y = 6 ⇒ y = 2
Answer: x = -10, y = 2, z = 6
Explain why the point (0,-5) is not located in quadrant IV
The point (0,-5) is not located in Quadrant IV because it has a negative y-coordinate.
Explanation:The point (0,-5) is not located in Quadrant IV because Quadrant IV is the bottom-right quadrant of the coordinate plane, where both the x-coordinate and the y-coordinate are positive. In Quadrant IV, the x-coordinate is positive and the y-coordinate is negative. A coordinate point with a negative y-coordinate would be located in Quadrants III or IV.
Learn more about Quadrants in the Coordinate Plane here:https://brainly.com/question/34164827
#SPJ2
Passes through A (1,5) and B (-8,9)
Given that the product of 22 integers is equal to 1, prove that their sum is not equal to 0.
1. If the product of these integers is to be 1, then all of them must be either 1 or -1.
2. Since the product is positive (+1), it must be that there are an *even* number of negative ones (-1), if any.
3. If the sum were 0 it would mean that the number of +1's must equal the number of -1's. So that means there would have to be exactly 22/2=11 of each.
4. But if there were 11 of each, that means the number of -1's would be *odd* and there's no way the product could be +1 (as stated in 2 above).
Hence, the sum is never 0, if the product of 22 integers is equal +1.
Fun problem.
We have a positive product, so no zero factors.
We have a positive product, so an even number of negative factors.
We have a product of 1, so all the integers must be either +1 or -1.
If we have 2n factors of -1 we have 22-2n factors of 1 so a sum of
[tex]s = (-1)2n + (1)(22-2n) = 22-4n[/tex]
For that to be zero we need
[tex]0 = 22-4n[/tex]
[tex]n = 22/4 = 11/2[/tex]
That's not an integer; we've shown there's no even number of -1s that will make the sum zero, and since there must be an even number of -1s, the sum cannot equal zero.